Kesiapsiagaan Anggota Pecinta Alam Dalam Mitigasi Bencana Gempabumi Di SMK Negeri 2 Surakarta - Prasetyo, Agil; , Drs. Suharjo M.S (2016)
Surakarta city including areas with high levels of vulnerability with a score of 60. SMK Negeri 2 Surakarta is one of the schools included in the area with high levels of disaster vulnerability. The purpose of this study was to determine the level of knowledge of nature lovers members in the earthquake disaster mitigation and know the non-structural mitigation in the face of the earthquake disaster which members nature lovers in SMK Negeri 2 Surakarta. Knowledge level of preparedness of the 30 Member Nature Lovers In Earthquake Disaster Mitigation in SMK Negeri 2 Surakarta obtained niliai composite index by 77.38%. The results showed that the level of knowledge about the earthquake disaster mitigation included in the high category. Non-structural mitigation measures carried out by another person or the school, but members nature lovers already know the purpose for which the nonstructural mitigation measures, and the students also helped in the passage of nonstructural mitigation.